Juan Antonio González-Iglesias, Eros es más, Madrid, Visor, 2007, 78 pp. - Paz González, Mario (Estudios Humanísticos. Filología, 2008)
Juan Antonio González-Iglesias, Eros es más, Madrid, Visor, 2007, 78 pp.